PRESTASI BELAJAR SISWA SMA DITINJAU DARI KEMAMPUAN KOMUNIKASI INTERPERSONAL GURU - Christian Tarkelin dan Sri Andjariah (Jurnal Psikologi, 2007)
One hundred and 26 grade 11 * students participated on this study in order to understand the contribution of teacher's ability on interpersonal community toward the student's academic performance. Teacher's good ability in communication would enhance student’s enthusiasm to learn more the subject. It was revealed that the relationship was quite low although significant (r(126) = .116. p » .036). The determinant coefficient was also low (2.59%). Several limitations and recommendations according to this low contribution of independent variable toward the dependent variable arc discussed.